First-Time Migration in Juvenile Common Cuckoos Documented by Satellite Tracking - Marta Lomas Vega; Mikkel Willemoes; Robert L. Thomson; Jere Tolvanen; Jarkko Rutila; Peter Samas; Roine Strandberg; Tomas Grim; Frode Fossøy; Bård Gunnar Stokke; Kasper Thorup (PUBLIC LIBRARY SCIENCE, 2022)
Being an obligate parasite, juvenile common cuckoos Cuculus canorus are thought to reach
their African wintering grounds from Palearctic breeding grounds without guidance from
experienced conspecifics but this has not been documented. We used satellite tracking to
study naïve migrating common cuckoos. Juvenile cuckoos left breeding sites in Finland
moving slowly and less consistently directed than adult cuckoos. Migration of the juveniles
(N = 5) was initiated later than adults (N = 20), was directed toward the southwest±significantly
different from the initial southeast direction of adults±and included strikingly long Baltic
Sea crossings (N = 3). After initial migration of juvenile cuckoos toward Poland, the
migration direction changed and proceeded due south, directly toward the winter grounds,
as revealed by a single tag transmitting until arrival in Northwest Angola where northern
adult cuckoos regularly winter. Compared to adults, the juvenile travelled straighter and
faster, potentially correcting for wind drift along the route. That both migration route and timing
differed from adults indicates that juvenile cuckoos are able to reach proper wintering
grounds independently, guided only by their innate migration programme.